(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Anaemia in pregnancy is a major public health problem in Nigeria. Iron deficiency is one of the major causes of anaemia in pregnancy. Inadequate iron intake during pregnancy can be dangerous to both baby and mother. Iron status of pregnant women was assessed in two rural and one urban communities in Cross River State Nigeria. Packed cell volume, haemoglobin, mean cell haemoglobin, mean cell haemoglobin concentration, red cell count, serum iron, total iron binding capacity, transferrin saturation, serum ferritin, soluble transferrin receptor and soluble transferrin receptor/ferritin ratio were measured in plasma/serum of 170 pregnant women within the age range of 15-45 years. Seventy participants were from antenatal clinic of University of Calabar Teaching Hospital Calabar (urban community), 50 from St Joseph Hospital Ikot Ene (rural community) in Akpabuyo Local Government Area and the remaining 50 from University of Calabar Teaching Hospital extension clinic in Okoyong (rural community), Odukpani Local Government Area of Cross River state. The prevalence of anaemia, iron deficiency, iron depletion and iron deficiency anaemia were found to be significantly higher (p<0.05) among pregnant women from the two rural communities when compared to the urban community. it was also observed that the prevalence of anaemia, iron deficiency, iron depletion and iron deficiency anaemia were significantly higher (p<0.05) among pregnant women from Akpabuyo 38(76.00%), 20(40.00%), 23(46.0%) , 16(32.00%) respectively followed by Okoyong 24(48.0%), 20(40.0%), 16(32.0%), 6(12.0) and then those from Calabar 14(20%), 12(17.90%) , 14(20.0%). The mean haemoglobin and haematocrit were significantly reduced (p<0.01) in pregnant women from the two rural communities. Serum iron, serum ferritin and transferrin saturation showed no significant difference while total iron binding capacity and soluble transferrin receptor significantly (p<0.01) increased among pregnant women from Okoyong when compared to those from Calabar. It was also shown that pregnant women in their third trimesters and multigravidae had the highest prevalence of iron depletion and iron deficiency anaemia while prevalence of iron deficiency and anaemia were higher in primigravidae and the pregnant women in their second trimester. In conclusion, this study has shown that the prevalence of anaemia and iron deficiency anaemia are higher among pregnant women in the rural communities when compared to those in the urban areas.